Hexagonal Boron Nitride‐Based Electrolyte Composite for Li‐Ion Battery Operation from Room Temperature to 150 °C. Issue 12 (9th April 2016) - Rodrigues, Marco‐Tulio F.; Kalaga, Kaushik; Gullapalli, Hemtej; Babu, Ganguli; Reddy, Arava Leela Mohana; Ajayan, Pulickel M.
Abstract : Batteries for high temperature applications capable of withstanding over 60 °C are still dominated by primary cells. Conventional rechargeable energy storage technologies which have exceptional performance at ambient temperatures employ volatile electrolytes and soft separators, resulting in catastrophic failure under heat. A composite electrolyte/separator is reported that holds the key to extend the capability of Li‐ion batteries to high temperatures. A stoichiometric mixture of hexagonal boron nitride, piperidinium‐based ionic liquid, and a lithium salt is formulated, with ionic conductivity reaching 3 mS cm −1, electrochemical stability up to 5 V and extended thermal stability. The composite is used in combination with conventional electrodes and demonstrates to be stable for over 600 cycles at 120 °C, with a total capacity fade of less than 3%. The ease of formulation along with superior thermal and electrochemical stability of this system extends the use of Li‐ion chemistries to applications beyond consumer electronics and electric vehicles. Abstract : A composite electrolyte based on hexagonal boron nitride and ionic liquid allows Li‐ion batteries to operate safely with outstanding performance in the range of 20–150 °C, being stable at high temperatures for over a month. The non‐flammability and negligible vapor pressure of the system presents a great solution for thermal management of Li‐ion batteries at extreme environments.